Doppler Sonography of Blood Flow Velocity in the Vertebral Arteries of Preterm and Term Neonates. (27th July 2016) - Windschall, Daniel; Hoekstra, Katrin; Haase, Roland
Abstract : Objectives: This study aimed to evaluate normal blood flow in the vertebral arteries and the basilar artery of preterm and term neonates by Doppler sonography. Methods: Blood flow in both vertebral arteries and the basilar artery was examined in 102 neonates between the biological ages of 28 and 41 weeks. Fifty‐one boys and 51 girls underwent Doppler sonography. Measurements were usually undertaken at 6 days old. Systolic and diastolic flow velocities, including the resistive index, were measured and analyzed, taking into consideration biological age, weight, and sex. Anatomic aberrations of the vertebral arteries were recorded. Results: Mean blood flow values ± SD in the basilar artery were 35.2 ± 7.4 cm/s (systolic velocity) and 10.9 ± 3.5 cm/s (diastolic velocity). Mean blood flow values in the right vertebral artery were 26.8 ± 9.3 cm/s (systolic velocity) and 8.0 ± 3.7 cm/s (diastolic velocity). Mean blood flow values in the left vertebral artery were 28.6 ± 8.3 cm/s (systolic velocity) and 8.7 ± 3.3 cm/s (diastolic velocity). Systolic and diastolic blood flow in both vertebral arteries was significantly higher from 38 to 41 weeks compared with 28 to 32 and 33 to 37 weeks ( P < .05). Regression analysis of systolic and diastolic blood flow velocities in the vertebral arteries versus biological age yielded significant results ( P < .05). Conclusions: Sonography is an excellent tool for examining blood flow in the basilar and vertebral arteries of premature and term neonates. Mean systolic and diastolic blood flow velocities in the vertebral arteries increase significantly with age.